Polymorphisms of Gene Cassette Promoters of the Class 1 Integron in Clinical Proteus Isolates - Xiao, Linlin; Wang, Xiaotong; Kong, Nana; Cao, Mei; Zhang, Long; Wei, Quhao; Liu, Weiwei (Frontiers in Microbiology, 2019)
Objective To describe the polymorphisms of gene cassette promoters of the class 1 integron in clinical Proteus isolates and their relationship with antibiotic resistance. Methods Polymorphisms of the gene cassette promoter in 153 strains of Proteus were analyzed by PCR and nucleotide sequencing. Variable regions of atypical class 1 integrons were detected by inverse PCR and nucleotide sequencing. Enterobacterial repetitive intergenic consensus (ERIC)-PCR was used to analyze the phylogenetic relationships of class 1 integron-positive clinical Proteus isolates. Representative beta-lactamase genes (bla), including blaTEM,blaSHV,blaCTX-M-1,blaCTX-M-2,blaCTX-M-8,blaCTX-M-9,blaCTX-M-25 and blaOXA-1, and plasmid-mediated quinolone resistance (PMQR) genes including qnrA, qnrB, qnrC, qnrD, qnrS, oqxA, oqxB, qepA, and aac(6′)-Ib were also screened using PCR and sequence analysis. Results Fifteen different gene cassette arrays and 20 different gene cassettes were detected in integron-positive strains. Of them, aadB-aadA2 (37/96) was the most common gene cassette array. Two of these gene cassette arrays (estX-psp-aadA2-cmlA1, estX-psp-aadA2-cmlA1-aadA1a-qacI-tnpA-sul3) have not previously been reported. Three different Pc-P2 variants (PcS, PcWTGN-10, PcH1) were detected among the 96 Proteus strains, with PcH1 being the most common (49/96). Strains carrying the promoters PcS or PcWTGN-10 were more resistant to sulfamethoxazole, gentamicin and tobramycin than those carrying PcH1. Strains with weak promoter (PcH1) harbored significantly more intra- and extra-integron antibiotic resistance genes than isolates with strong promoter (PcWTGN-10). Further, among 153 isolates, representative beta-lactamase genes were detected in 70 isolates (blaTEM-1, 54; blaOXA-1, 40; blaCTX-M-3, 12; blaCTX-M-14, 12; blaCTX-M-65, 5; blaCTX-M-15, 2) and representative PMQR genes were detected in 87 isolates (qnrA, 6; qnrB, 3; qnrC, 5; qnrD, 46; qnrS, 5; oqxA, 7; aac(6′)-Ib, 13; aac(6′)-Ib-cr, 32). Conclusion To the best of our knowledge, this study provides the first evidence for polymorphisms of the class 1 integron variable promoter in clinical Proteus isolates, which generally contain relatively strong promoters. Resistance genotypes showed a higher coincidence rate with the drug-resistant phenotype in strong-promoter-containing strains, resulting in an ability to confer strong resistance to antibiotics among host bacteria and a relatively limited ability to capture gene cassettes. Moreover, strains with relatively weak integron promoters can “afford” a heavier “extra-integron antibiotic resistance gene load”. Furthermore, the gene cassettes estX, psp and the gene cassette arrays estX-psp-aadA2-cmlA1, estX-psp-aadA2-cmlA1-aadA1a-qacI-tnpA-sul3 have been confirmed for the first time in clinical Proteus isolates. Beta-lactamase genes and PMQR were investigated, and blaTEM-1 and blaOXA-1 were the most common, with qnrD and aac (6′)-Ib-cr also being dominant.